Remediation of cadmium by Indian mustard (Brassica juncea L.) from cadmium contaminated soil: a phytoextraction study - Bhadkariya, Rajeev Kumar; Jain, VK; Chak, GPS; Gupta, SK (International Journal of Environment, 2014)
Cadmium is a toxic metal for living organisms and an environmental contaminant. Soils in many parts of the world are slightly too moderately contaminated by Cd due to long term use and disposal of Cd-contaminated wastes. Cost effective technologies are needed to remove cadmium from the contaminated sites. Soil phytoextraction is engineering based, low cost and socially accepted developing technology that uses plants to clean up contaminants in soils. This technology can be adopted as a remediation of cadmium from Cd-contaminated soils with the help of Brassica juncea plant. The objective of this work was to evaluate the cadmium (Cd) accumulate and the tolerance of Brassica juncea. The Cd accumulates in all parts of plants (roots, stems and leaves). It was found that accumulating efficiency increased with the increase in the concentration of applied cadmium metal solution. Maximum accumulation of cadmium was found in roots than stem and leaves. Phytoextraction coefficient and translocation factor were highest to show the validity of the Brassica juncea species for hyperaccumulation of the Cd metal. These results suggested that Brassica juncea has a high ability to tolerate and accumulate Cd, so it might be a promising plant to be used for phytoextraction of Cd contaminated soil. DOI: http://dx.doi.org/10.3126/ije.v3i2.10533 International Journal of the Environment Vol.3(2) 2014: 229-237